Valence state conversion of Mn ions in Li2O–ZnO-GeO2 glass-ceramics: Spectral, structural, ESR and XRF studies; Ceramics International; Vol. 50, iss. 11, Pt. B - Kulpina E. V.; Babkina A. N. Anastasiya Nikolaevna; Zyryanova K. S. Kseniya Sergeevna; Kuzmenko N. K. Nataljya Konstantinovna; Ignatjev A. I. Aleksandr Ivanovich; Valiev D. T. Damir Talgatovich; Stepanov S. A. Sergey Aleksandrovich; Pankin D. O. Dmitry Olegovich; Povolotskaya A. Anastasiya; Platonova N. V. Nataliya Vladimirovna; Shendrik R. Roman (2024, 2024)
Title screen